Studies on the livestock of southern Darfur, Sudan. IV. Production traits in goats - Wilson, R.T. (Springer, 1976)
Discusses the results of a study on goat production under indigenous management conditions in southern Darfur, Sudan. Seven flocks of indigenous goats were studied over a period of 15 months. Birth rates in the region approached 2.1 kids per doe per year. A high total offtake of 28 percent and a weighted average death rate of about 16.5 percent were observed. Mortality in kids was unrelated to number of births. Weighted average rate of gain for all surviving kids was 87 g per day to 3 months and 67 g per day to 6 months of age. The growth rates of twin and single kids were similar, but triplet kids grew at a slower rate. For each kilogramme liveweight of breeding females, goats produced 1.5 and 8 times the weight of meat produced by sheep and cattle respectively under the same management and environmental conditions.